What Is Reduction in Phenomenology, Really? An Attempt to Get to the Essence of the Phenomenon - Marius Bytautas (International Journal of Qualitative Methods)
Since the late 1970s, phenomenology has been widely used in nursing, education, psychology, and other disciplines. As one should have expected, its increasing popularity made this methodology vulnerable to criticism. Various authors began to question the credibility and usefulness of phenomenological research. Among the arguments, the vagueness of central concepts is the most notable. Indeed, concepts such as reduction have been interpreted in different ways, including many misleading interpretations. This article is an attempt to define reduction in phenomenology in the face of reductionism. Employing van Riel’s definition of reduction, I argue that reduction in phenomenology fits well within the boundaries of reductionism. I further explain that reduction in phenomenology is a reduction of a phenomenon, but not a reduction of an experience. That is, the phenomenon, partially accessible through experience, is reduced to its essence, and the essence should be understood as the necessary and sufficient qualities of the phenomenon. In addition, a structural examination of the many moves of reduction that were described by Husserl and van Manen is presented, contrasting them to the types of reduction in phenomenology, which are also described. These are: first-person and second-person reduction. Furthermore, the modalities through which these types are experienced are explored. In conclusion, I argue that reduction in phenomenology is by itself a lived phenomenon. Therefore, this paper can be regarded as a reduction of the phenomenon of reduction.